The Correlation Between Rates of Falling, Balance, Quality of Life and Fear of Falling in Patients With Chronic Stroke - Hamid Azadeh; Atefeh Fekri; Hamid Amraie; Meysam Roostaei; Hamzeh Baharlouei (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Stroke is one of the most important causes of disability worldwide. Fear of falling is one of the consequences of stroke that could decrease the quality of life. It presents in the patients who have fallen as well as in patients had not experienced a fall. Fear of falling is essential because of its impact on physical and mental health and even the quality of life. In addition to adverse effects of fear of falling on the patient, it may have a significant impact on the family quality of life. There are few published studies about the fear of falling after stroke, but given its significant implications for quality of life in patients, more studies are needed to improve the knowledge about the correlation of fear of falling and quality of life. The findings could help identify people at risk and also develop the prevention strategy in the management of fear of falling and quality of life. Previous studies assessed the acute and subacute patients with stroke and the authors could not find any research conducted with chronic subjects. Also, they measured the correlation between fear of falling and personal characteristics of participants and there is lack of evidence about the correlation between fear of falling with the rate of falling, postural control and SF-36. The objective of the current study was to examine the relationships between the fear of falling and rate of falling, balance, and quality of life in patients with chronic stroke.  Materials & Methods The subjects (n=44, 20 males and 24 females) were selected based on the convenience sampling method from the patients who referred rehabilitation clinics. The inclusion criteria were individuals within at least six months after the stroke, unilateral signs, ability to walk independently and the exclusion criteria were metabolic or rheumatologic disease, lower extremity deformities, cognitive impairments and visual impairments. The participants completed a demographic form consisting of age, gender, height, weight, comorbidities, education, and the duration of the stroke, affected side, dominant side and rate of falls in last year. The fear of the falling and quality of life was measured using Fall Efficacy Scale- International and SF-36, respectively. Functional reach test and timed up and go were conducted for balance assessing. The Spearman's correlation was used to find whether there are significant relationships between fear of falling and other variables.  Results The Pearson analysis showed correlation between Fall Efficacy Scale- International and timed up and go (P<0.001) and Functional reach test (P=0.03) scores and some subscales of SF-36 including physical functioning (P<0.001), role limitations due to physical health (P<0.001) and physical component (P<0.001).However, this association was not observed with the rate of falling (P=0.015), pain (P=0.42), general health (P=0.12), energy (P=0.09), social function (P=0.30) and role limitations due to emotional problems (P=0.24) and metal component (P=0.41). Conclusion The findings of the present study demonstrated the correlation between balance, physical dimensions of quality of life and fear of falling in patients with stroke; however, the rate of falling has no association with fear of falling.